Televisi Mendidik Karakter Bangsa: Harapan dan Tantangan - Oos M Anwas (Jurnal Pendidikan dan Kebudayaan, 2010)
Character education is an effort to embed intelligence in thinking, appreciation in attitude, and practice in the form of behavior which is consistent with the values and norms as well as noble personality. Therefore we need inuring, modeling, and a conducive environment within family, school, community, and support from the mass media, especially television exposure. The school principal, teachers, parents, and communities are required to be role models for younger generations. However, habituation and ideals in the daily behavior are not easy. Television media with different characteristics is hopefully able to minimize these constraints. Television is the most popular mass media. Television also can dramatize and photograph the reality of everyday life in society in audio-visual based. The reality mentioned here comprises the appreciation and cultivation of religious teachings, the nation’s cultural diversity, local knowledge, natural resources, social life, development of creativity, including the history of national struggle and folklore. Certain presentation format could optimize the concept of drama, soap opera, or a true story. Characterization and location setting describe Indonesian territory that accommodate the diversity culture, ethnic, religion, and the local environment. The role of community is very important to influence television station in order to broadcast educating programs. Similarly, government commitment and policy as well as private concerns is expected i order to instill character education through television. ABSTRAK Pendidikan karakter merupakan upaya menanamkan kecerdasan dalam berpikir, penghayatan dalam bersikap, dan pengamalan dalam bentuk perilaku yang sesuai dengan nilai-nilai dan norma serta akhlak mulia. Oleh karena itu, diperlukan pembiasaan, keteladanan, dan lingkungan yang kondusif baik di keluarga, sekolah, masyarakat, serta dukungan exposure media massa khususnya televisi. Kepala sekolah, guru, orangtua, dan masyarakat dituntut menjadi teladan bagi generasi muda. Namun, pembiasaan dan keteladanan dalam berperilaku sehari-hari tidak mudah. Media televisi dengan berbagai karakteristiknya optimis dapat meminimalisir kendala tersebut. Televisi merupakan media massa yang paling digemari. Televisi juga dapat mendramatisasi dan memotret realitas kehidupan sehari-hari di masyarakat dalam bentuk audio visual. Realitas tersebut merupakan penghayatan dan penanaman ajaran agama, keanekaragaman budaya bangsa, kearifan lokal, kekayaan alam, kehidupan sosial kemasyarakatan, pengembangan kreativitas, termasuk sejarah perjuangan bangsa dan cerita-cerita rakyat. Format sajian dapat mengoptimalkan konsep drama, sinetron, atau kisah nyata. Penokohan dan setting lokasi menggambarkan wilayah Indonesia dengan mengakomodir keragaman budaya, suku, agama, dan lingkungan lokal. Untuk mewujudkan harapan ini peran masyarakat sangat penting dalam mempengaruhi stasiun televisi untuk menyiarkan acara yang mendidik. Begitu pula diperlukan komitmen dan kebijakan pemerintah, serta kepedulian swasta dalam menanamkan pendidikan karakter melalui televisi.